2013
DOI: 10.1002/eji.201343600
|View full text |Cite
|
Sign up to set email alerts
|

Carbon monoxide decreases endosome–lysosome fusion and inhibits soluble antigen presentation by dendritic cells to T cells.

Abstract: Heme oxygenase-1 (HO-1) inhibits immune responses and inflammatory reactions via the catabolism of heme into carbon monoxide (CO), Fe 2+ , and biliverdin. We have previously shown that either induction of HO-1 or treatment with exogenous CO inhibits LPS-induced maturation of dendritic cells (DCs) and protects in vivo and in vitro antigenspecific inflammation. Here, we evaluated the capacity of HO-1 and CO to regulate antigen presentation on MHC class I and MHC class II molecules by LPS-treated DCs. We observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
41
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 61 publications
9
41
3
Order By: Relevance
“…Thus, mitochondrial dysfunction is not associated with reduced DCs maturation, because the stability of this organelle is not directly associated with these routes. Moreover, this notion agrees with our previous [21] and current report where CO-mediated mitochondrial dysfunction did not impair LPS-induced maturation.Although in a previous report we have shown that CO did not significantly impair OVA degradation [21], here we show single-endosome data supporting that CO can impair antigen processing. An explanation for these apparent discrepancies consists of differences in the experimental settings between studies.…”
supporting
confidence: 94%
See 1 more Smart Citation
“…Thus, mitochondrial dysfunction is not associated with reduced DCs maturation, because the stability of this organelle is not directly associated with these routes. Moreover, this notion agrees with our previous [21] and current report where CO-mediated mitochondrial dysfunction did not impair LPS-induced maturation.Although in a previous report we have shown that CO did not significantly impair OVA degradation [21], here we show single-endosome data supporting that CO can impair antigen processing. An explanation for these apparent discrepancies consists of differences in the experimental settings between studies.…”
supporting
confidence: 94%
“…1F-G). These results support our previous findings, where CO was unable to dampen these same processes [21], suggesting that mitochondrial function might not be involved in nonantigenic inflammatory routes in DCs. Next, we searched for the mitochondria-independent mechanism that sustained these processes.…”
supporting
confidence: 92%
“…As previously reported, OVA coupled to Alexa647 and BSA coupled to DQ-Red were used to analyze antigen uptake and antigen degradation, respectively. 18,[22][23][24] The flow cytometry gating strategy from one representative experiment for OVA uptake and BSA degradation by CD11c…”
Section: Size 20 Nm Ps Particles Modulate Antigen Degradation In Bmdcsmentioning
confidence: 99%
“…Despite the encouraging finding that CO produced a marked decrease in IFN-g mRNA levels in kidney, this reduction did not achieve statistical significance (P = 0.0577). In addition, CO treatment would also modulate the activation and maturation of DCs and macrophages leading to reduced levels of proinflammatory cytokines such as IL-6, IL-12 and IL-18, as observed in CO-treated mice [37]. However, the precise contribution of activated B220 1 CD3 1 CD4 2 T cells to kidney and lung injury remains to be elucidated, as well as whether CO could modulate activated T cell recruitment directly in glomerulus.…”
mentioning
confidence: 99%